‘Th’angelic train’ : Evangelicals, the Black Lives Matter Movement, and the Anti-racist Christianity of Phillis Wheatley and Quobna Ottobah Cugoano (Article Commentary) - Gentry, Victoria Ramirez (2021)
On September 17, 2020, President Donald Trump spoke at the National Archives Museum for the White House Conference on American History and quoted Martin Luther King Jr.: “We embrace the vision of Martin Luther King, where children are not judged by the color of their skin but by the content of their character.”1 After misusing King to establish his point, Trump launched into his critique of “the left” and what he termed Critical Race Theory2: “By viewing every issue through the lens of race, [the left] want to impose a new segregation . . . Critical race theory, the 1619 Project, and the crusade against American history is toxic propaganda, ideological poison.”3 This evoking of King’s memory to denounce Critical Race Theory reimagines both American history and Black peoples’ experiences in two different ways. First, Trump defines recognition of racism in American history as racist itself, perversely branding the pursuit of inclusion and diversity as segregation. Secondly, Trump neutralizes King as a proponent of nonviolence and compliance, ignoring the fact that King was arrested and beaten while fighting for civil rights.4 Further, Trump positions Critical Race Theory as a threat to Christianity, asserting that it views “hard work, rational thinking, the nuclear family, and belief in God” as “aspects of ‘whiteness.’”5 In this statement, Trump frames the efforts of anti-racism as an attack against Christianity itself. Specifically, Trump uses King, a Black man, to uphold white supremacist ideologies while asserting that standing up for the rights of Black individuals is anti-Christian.